Hubungan pelatih-atlet: Studi fenomenologis tentang persepsi atlet Paralimpiade Indonesia - Noor Azizah Dwi Agustin; Sugiyanto Sugiyanto; Febriani Fajar Ekawati (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
A strong coach–athlete relationship is essential for achieving optimal performance, particularly in Paralympic sports where athletes face physical limitations and social barriers. Coaches play roles that extend beyond technical instruction by providing emotional support, motivation, and adaptive strategies tailored to individual disability needs. This study aims to understand how Indonesian Paralympic athletes interpret their relationships with their coaches based on their lived experiences. A qualitative phenomenological approach was used with three Indonesian Paralympic athletes actively training for the 2024 Paris Paralympics: one athlete with a visual disability, one with a physical disability, and one with an intellectual disability. Data were collected through in-depth interviews, observations, and analysis of coaching documentation, which were processed using a phenomenological analysis procedure. The results show that the coach–athlete relationship is characterized by emotional closeness, mutual commitment, reciprocal role support, and alignment of goals. Athletes perceive their coaches as figures who listen, understand their conditions, and provide both psychological and practical assistance during training. Coaches adjust communication styles and coaching strategies to meet athletes' sensory and cognitive needs, enabling athletes to stay motivated and confident. Shared goal-setting further enhances cooperation and strengthens athletes' readiness for competition. This study concludes that the coach–athlete relationship in the Indonesian Paralympic context involves emotional, adaptive, and goal-oriented interactions that serve as a foundation for inclusive and high-performance coaching. These findings offer practical insights for enhancing coaching development programs that prioritize interpersonal sensitivity and support athletes' overall well-being.